Lack of utility of nasopharyngeal swabs for diagnosis of Burkholderia pseudomallei pneumonia in paediatric patients - Hearn, P; Turner, C; Suy, K; Soeng, S; Day, N; Turner, P (Oxford University Press, 2016)
Diagnosis of Burkholderia pseudomallei pneumonia in children is challenging. We investigated the utility of nasopharyngeal swabs taken from 194 paediatric patients on admission with radiologically proven pneumonia. Melioidosis was proven in 0.5% of samples tested and only in a third of those known to be bacteraemic with B. pseudomallei. It appears unlikely that culture of nasopharyngeal secretions is helpful to confirm B. pseudomallei pneumonia in paediatric patients.